Non‐laser treatment for tattoo removal. (9th February 2022) - Dash, Gaurav; Patil, Anant; Kassir, Martin; Goldman, Mitchel P.; Gold, Michael H.; Adatto, Maurice; Große‐Büning, Stephan; Grabbe, Stephan; Goldust, Mohamad
Abstract: Tattoos are increasingly gathering attention in the young population, especially in second to fourth decade of life. With such trends, rate of its removal also has been on the rise. Treatment options for tattoo removal besides lasers are surgery, radiofrequency, infrared light, cryotherapy, dermabrasion and salabrasion. Unfortunately, none of these procedures are associated with satisfactory cosmetic results due to adverse effects such as scarring and dyspigmentation. Although laser treatment has become the gold standard for tattoo removal, it is also associated with some limitations. Some tattoo inks are resistant to laser, and multiple sessions and multiple wavelengths may be required for its complete removal. Considering these limitations, other treatment modalities for tattoo removal must be explored. This article highlights the non‐laser treatment options for tattoo removal. We reviewed all published literature identified from electronic databases (MEDLINE and PubMed) till August 2021 to highlight the non‐laser treatment options for tattoo removal.